Lizzo’s Black, Female, and Fat Resistance - Pickett Miller, Niya. author. aut Link
VI, 72 p. 1 illus.
Keywords: “What does it mean to flaunt a body which refuses to be shamed? This timely and important study explores the singer-songwriter and musician, Lizzo’s ‘flaunting’ as an emancipatory act. A central concern of the book is how Lizzo energises an intersectional space of Black, Fat, and Female through her hyper-embodiment: it addresses a serious shortfall of meaningful and sustained intersectional analysis without which any understanding of social justice and embodiment is dangerously lacking. A good read for scholars of weight, race, celebrity culture and those interested in new configurations of stigma.” — Jayne Raisborough, Professor of Media and Cultural Studies, Leeds Beckett University, UK, and author of Fat Bodies, Health and the Media (2016) Celebrated musician and entertainer Lizzo wowed audiences and left many “feeling good as hell.” Notwithstanding her collective—fat, Black female— identity she catapulted into mainstream success while redefining the social script for body size, race, and gender. This book explores a tale of two narratives: Lizzo’s self-curated, fat-positive identity and the media’s reaction to an unabashedly proud fat, Black woman. This critical analysis examines how Lizzo challenges fatphobia and reconstitutes fat stigmatization into self-empowerment through her strategic use of hyper-embodiment via social media, and the rhetorical distinctions between Lizzo’s self-curated narrative via social media and those offered about her in print media. In part, Lizzo’s bodily flaunting is argued as a significant rhetorical act that emancipates her identity of fatness and reframes the negative tropes of (fat) Black women typically curated in American culture. Niya Pickett Miller, Ph.D., is a public speaker and post-doctoral Assistant Professor of Communication Studies in the Department of Communication and Media at Samford University, USA.Her forthcoming edited book (2021) titled, #Verzuz and Club Quarantine: Sustaining Black Music and Black Culture During COVID-19 features curated studies of Black cultural expression and communication through live streamed music on Instagram during the COVID-19 pandemic. Her 2020 book, Deconstructing Albinism as the Other, explores the visual tropes of people with albinism in American popular culture. Gheni N. Platenburg, Ph.D., is an Assistant Professor in the School of Communication and Journalism at Auburn University, USA, where she teaches multimedia journalism courses. Her research interests primarily fall at the intersection of race and media. Her co-authored research has been published in the peer-reviewed Journal of Black Studies. Currently, she works as a freelance journalist for The Washington Post Talent Network.